THE APPLICATION OF MARKOVS STOCHASTIC PROCESSES IN RISK ASSESSMENT FOR ACCOUNTING INFORMATION SYSTEMS - Milojević, Ivan; Ignjatijević, Svetlana; Micić, Ivan (Economics of Agriculture, 2017)
Almost all processes in the area of business management, especially those of determining reliability of the accounting-information system in business management are connected with certain risk, i.e. they are of a stochastic character, which means that every method for solving these problems must be related to the probability theory and corresponding mathematical-statistical methods. This is why it can be noted that only reliable means for determining the reliability rate of the accounting information system are corresponding mathematical-statistical methods. Having this in mind, in this paper we tried to have the problem of forming the risk rate in the area of reliability of the accounting system solved by applying methods based on stochastic processes of Markovs type.